Dreamworks: Werden Bilder Realität? - Omahna, Manfred (Österreichische Zeitschrift für Geschichtswissenschaften, 2001)
The development pattern of American suburbs would appear to be copied from images constructed by Hollywood. The familiar image of the one-family house, which is closely linked to the middle-class family, progress and rypresentations of property, is idealized in current architecture as New Urbanism (for example, by Elisabeth Plater-Zyberk and Andres Duany). lt seems to be the case that this elite form of living can simply be planted onto urban peripheries in westernized coun- tries as a kind of >instant city<, without any consideration for local historical and cultural characteristics. However, the subjective circumstances in which people live indicate the possibilities of cultural uniqueness in the face of conceptual homogenization.